Legal aspects of social protection of military personnel in ukraine in the context of modern challenges - V. Kurylo; I. Kurylo; V. Mushenok (Law. Human. Environment, 2025)
The study is devoted to the legal issues of social protection of military personnel in Ukraine in the context of current challenges, particularly the ongoing military aggression. The main objective of the study was to conduct a comprehensive analysis of the effectiveness of the social protection system for the military, identify key problems of legal regulation and practical implementation of social guarantees. The study used the comparative legal method, systemic analysis and analysis of regulatory legal acts, which identified the main shortcomings of the current legislation and study international experience in the field of social protection. The study determined that military personnel are one of the most vulnerable categories of the population facing risks to lives and health. The main challenges that negatively affect their social protection are an imperfect legal framework, fragmented legislation and existing bureaucratic barriers. The study also revealed imperfections in reintegration programmes, which negatively affected the adaptation of veterans in the post-war period. One of the biggest challenges is the lack of funding for social programmes and initiatives. To improve the social protection system, recommendations are made to modernise legislation, including the harmonisation of national norms with international standards, and the introduction of effective mechanisms for payments and benefits. It is also necessary to develop comprehensive programmes for psychological support and vocational rehabilitation of veterans, incorporating specific needs. Ensuring effective social protection of servicemen requires not only legislative reform but also a comprehensive approach to their support at all stages of service and adaptation to civilian life